Reconstruction of The Epistemology of Qur’anic Moral Education In At-Tibyan By Imam An-Nawawi and Its Relevance for Contemporary Islamic Education - Anugrah Gustiranda; Ahsan Hakim (Jurnal Pendidikan Indonesia, 2026)
Contemporary Islamic education faces epistemological challenges in the form of reducing education to cognitive achievement, fragmenting knowledge and moral character, and weakening the transcendental orientation in Qur’anic learning. This condition has generated a crisis of meaning and value disorientation, despite the quantitative growth of Islamic educational institutions. This study aims to reconstruct the epistemological structure of Qur’anic moral education formulated by Imam An-Nawawi in At-Tibyan fi Adabi Ḥamalat al-Qur’an and to analyze its relevance for the renewal of contemporary Islamic education. Employing a qualitative approach with a library research method, this study is based on thematic analysis and philosophical hermeneutics of At-Tibyan, enriched by critical dialogue with classical and contemporary theories of Islamic education. The findings reveal that Imam an-Nawawi systematically reconstructs the epistemology of Islamic education by affirming five core elements: a theologically transcendental source of knowledge; the epistemic subject as the bearer of the trust of revelation; the object of knowledge as the Qur’an understood as a normatively binding moral truth; methods of knowledge acquisition oriented toward the internalization of adab and ethical praxis; and the ultimate educational aim of forming a Qur’anic person who is both knowledgeable and morally upright. Within this structure, adab is positioned as the foundation, medium, and indicator of the validity of knowledge, thereby rejecting the reduction of knowledge to purely cognitive understanding detached from moral consequences. These findings are relevant as an alternative epistemological framework for contemporary Islamic education, enabling it to move beyond technocratism and formalism toward the integration of knowledge, adab, and moral-social responsibility.